GAMBARAN LAYANAN BIMBINGAN KELOMPOK MELALUI MEDIA ZOOM MEETING UNTUK KEMATANGAN KARIR SISWA SMA - Nadia Nurazizah; Asep Samsudin; Tita Rosita (IKIP Siliwangi, 2022)
This study aims to determine the description of group guidance services through the media zoom meeting for career maturity of high school students who experience a low understanding of the development of students' abilities at SMA Negeri 1 Cibuaya in Cibuaya District, Karawang Regency, West Java. The method used is descriptive qualitative research method. This study uses an inductive approach in which the data in this study are descriptive data which are generally in the form of words and pictures. With data collection techniques using interviews and observation. The subjects of this study were two class XII students of SMA Negeri 1 Cibuaya who experienced career immaturity. Based on the results of the study, it was shown that the two students experienced career immaturity because they were still confused and had difficulty making their choices or in making career decisions and had not yet reached a good level of maturity in the sense that there were still many shortcomings possessed by class XII students, which mainly concerns on career information so that it can be said that the maturity of class XII at SMA Negeri 1 Cibuaya is still not mature enough. For this reason, group guidance is needed in an effort to increase the career maturity of SMA Negeri 1 Cibuaya students.Keywords: Group Guidance Service, Career Maturity, Zoom Meeting